Contrasting mechanisms of regulating translation of specific Drosophila germline mRNAs at the level of 5′-cap structure binding. (26th October 2005) - Lasko, P.; Cho, P.; Poulin, F.; Sonenberg, N.
Abstract : Translational control is a key genetic regulatory mechanism underlying the initial establishment of the major spatial axes of the Drosophila embryo. Many translational control mechanisms target eIF4E (eukaryotic initiation factor 4E), an initiation factor that recognizes the 5′-cap structure of the mRNA. Cap recognition by eIF4E, in complex with eIF4G, is essential for recruitment of the mRNA to the small ribosomal subunit. One established mechanism for repressing translation involves eIF4E-binding proteins, which competitively inhibit the eIF4E–eIF4G interaction. Our group has uncovered a novel mechanism for repression in which an eIF4E cognate protein called d4EHP, which cannot bind eIF4G, binds to the 5′-cap structure of cad mRNA thus rendering it translationally inactive. These two related, but distinct, mechanisms are discussed and contrasted in this review.